Low-temperature Rankine cycle to increase waste heat recovery from the internal combustion engine cooling system. (15th February 2019) - Mashadi, Behrooz; Kakaee, Amirhasan; Jafari Horestani, Ahmad
Highlights: Absorption of total waste heat of the engine cooling system. Determining the matching conditions between a low-temperature Rankine cycle and an engine cooling system. Choosing the appropriate working fluid. Achieving more work with a lower mass flow rate in the low-temperature Rankine cycle. Abstract: By focusing on the increase of the input energy, a recovery system is introduced, in which a combination between the internal combustion engine cooling system and a low-temperature Rankine cycle is established. The entire waste heat of the engine cooling fluid is absorbed in the low-temperature Rankine cycle through a low mass flow rate of the working fluid. This not only leads to increased efficiency and power of the system, but also to a smaller size for the recovery system. This system is shown to recover more than 57% of the available energy in the cooling fluid. In addition, the traditional radiator of the engine cooling system is eliminated. By the application of the thermodynamic analysis to 19 different working fluids, appropriate matching conditions between the low-temperature Rankine cycle with the engine cooling system and the properties of the working fluid were examined. It was concluded that, Ammonia had the highest compatibility with the proposed system. The analysis of the sensitivity of the ambient temperature for the low-temperature Rankine cycle was performed with Ammonia as the working fluid, and it was observed that a variation in the ambient temperature has a small effect on the cooling fluid temperature. Finally, the results derived from the low-temperature Rankine cycle were compared with the results available from six other research work. This comparison showed that the extent to which it is possible to obtain the available energy in the cooling system by the proposed system with a low mass flow rate is much higher than those obtained by those six researches.